Filling the palaeobiogeographic gap in mysticetes evolution: New records of baleen whales from the Neogene of the Atacama region, southeastern Pacific, Chile - Gutstein, Carolina; Buono, Mónica Romina
Mysticetes are an iconic group of marine mammals that include the most gigantic microphagous vertebrates that have ever lived on Earth. The fossil record of baleen whales dates back to the early Oligocene, reaching a diversification and widespread distribution during the Miocene, being present along most of the oceans (Atlantic, North and southwestern Pacific, and the Mediterranean). However, along the southeastern Pacific, especially at the Chilean coast, the fossil record of baleen whales remains a mystery. In recent years we increased fieldwork efforts in the Neogene Bahía Inglesa and Coquimbo formations, and performed a critical review of fossil specimens from national collections. Fil: Gutstein, Carolina. Universidad de Santiago de Chile. Facultad de Ciencias. Departamento de Biología. Laboratorio de Biología del Desarrollo; Chile. Consultora Paleosuchus Limitada; Chile Fil: Buono, Mónica Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto Patagónico de Geología y Paleontología; Argentina 64th Palaeontological Association Annual Meeting Oxford Reino Unido The Palaeontological Association Oxford University Museum of Natural History